The Influence of School Principal Leadership, Teacher Competence, And School Organizational Culture on Teacher Performance, As Well As Its Implications for Graduate Competencies Moderated By Infrastructure Facilities - Kurniasih, Nia (Journal of Business Management Education (JBME), 2024)
This study analyzes the influence of principal leadership, teacher competence, and school organizational culture on teacher performance, as well as its implications on graduate competencies moderated by infrastructure. The study was carried out at a Private Vocational School with Accreditation B status in the area of the Branch of the Education Office VI of West Java Province, especially in Cianjur Regency and West Bandung Regency. The respondents were 212 teachers who were selected using the cluster proportional random sampling technique from a total population of 457 teachers. A quantitative approach with descriptive and verifiable methods was used in this study, with data analysis using scale ranges and path analysis through SPSS software. The results of the study show that the leadership of the principal makes the most dominant contribution to teacher performance by 35%, followed by teacher competence at 20.7%, and school organizational culture at 15.6%. Overall, the three independent variables had an effect of 70.8% on teacher performance. Teacher performance had an effect of 73.2% on the competence of graduates, with infrastructure as the moderator variable that strengthened the relationship by 80.1%.